The impact of organisational knowledge and knowledge sharing on the quality of downsizing and restructuring outcomes - Sitlington, Helen; Marshall, Verena (Monash University, 2011)
This study considers the impact of formal knowledge sharing and informal networks on the level of organisational knowledge and effectiveness after downsizing or restructuring. These variables are examined as they are perceived by employees, both decision makers and implementers and affected employees. Previous research indicates that only one-third of organisations report increased productivity, as a result of the downsizing and restructuring strategies, while 50% report decreased labour costs, and less than 20% report increased labour flexibility (Lee & Corbett, 2006; Cascio 2002) as a result of downsizing and restructuring strategies. It is proposed that many of the reported issues are associated with the loss of knowledge and knowledge-sharing networks that occur during downsizing/restructuring. Although much has been written about knowledge, knowledge sharing and informal networks in organisations, little attention is paid in the literature to loss of knowledge or network breakdown in this context. This study seeks to redress this gap in the literature, through investigating the impact of organisational knowledge, through formal and informal knowledge sharing, on perceived organisational effectiveness after downsizing or restructuring has taken place.